A framework for curating personalised leisure walking experiences - Williams, James F. L. (2025)
How can a richer understanding of the leisure walking experience be used to support the curation of personalised route recommendations? Leisure walking is a personal and subjective experience that encompasses a range of multi-faceted expectations and narratives, this can include visiting points of interests, connecting with the environment, or engaging with the social fabric of places. The broad and disparate scope of these reasons and interests makes the process of recommending new and personalised leisure walking experiences difficult. Existing research exploring the recommendation of leisure walking experiences is often based on broad assumptions about walkers with little representation of subjective or contextual detail. Prior work in leisure walking fails to address the wide array of reasons for leisure walking and in turn representing these in personalised walking experiences. Based on the lack of personalisation of leisure walking experiences, this thesis investigates leisure walking from a user-centred perspective. Three grounded theory studies are conducted to understand leisure walking, capturing details on (1) leisure walking behaviours through a behaviour survey, (2) practitioner knowledge of the subject area through interviews with professionals, and (3) a rich understanding of the leisure walking experience through a think-aloud study.